2014
DOI: 10.1039/c3tc32418d
|View full text |Cite
|
Sign up to set email alerts
|

Hollow cathode plasma-assisted atomic layer deposition of crystalline AlN, GaN and AlxGa1−xN thin films at low temperatures

Abstract: The authors report on the use of hollow cathode plasma for low-temperature plasma-assisted atomic layer deposition (PA-ALD) of crystalline AlN, GaN and AlxGa1−xN thin films with low impurity concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
177
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 147 publications
(194 citation statements)
references
References 66 publications
(76 reference statements)
13
177
4
Order By: Relevance
“…Figure 2 shows the C can also be similarly decomposed into two components at 396.37 and 394.57 eV, which is assigned to the N-Ga bond and Auger Ga peaks. 12 Although the spectral locations and intensities of Ga 3d and N 1s peaks were found to be slightly different for GaN samples grown at 450 C, the atomic composition of GaN film was hardly changed. The HR-XPS spectrum of Ga 3d [ Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 2 shows the C can also be similarly decomposed into two components at 396.37 and 394.57 eV, which is assigned to the N-Ga bond and Auger Ga peaks. 12 Although the spectral locations and intensities of Ga 3d and N 1s peaks were found to be slightly different for GaN samples grown at 450 C, the atomic composition of GaN film was hardly changed. The HR-XPS spectrum of Ga 3d [ Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2(c)] for GaN film grown at 450 C was fitted by two subpeaks located at 20.10 and 19.15 eV, corresponding to Ga-N bonds. 12 The N 1s spectrum [ Fig. 2(d)] obtained for GaN grown at 450 C was fitted similarly using two subpeaks located at 397.49 and 395.67 eV, corresponding to N-Ga and Auger Ga bonds, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Results and discussion 3.1 AlN, GaN and Al x Ga 1-x N thin films and nanostructures In a recent study, we demonstrated the HCPA-ALD of crystalline AlN, GaN and Al x Ga 1-x N thin films at low temperature (i.e., 200 °C) using trimethylmetal precursors and NH 3 or N 2 /H 2 plasma [14]. Depositions carried out using non-optimized parameters resulted in AlN and GaN films with wafer-level non-uniformities < ±1.5%.…”
Section: Characterization Methodsmentioning
confidence: 99%
“…Recently, we showed that ALD-grown III-nitride thin films may suffer from plasma-related oxygen contamination depending on the choice of N-containing plasma gas (N 2 , N 2 /H 2 or NH 3 ) [12,13]. Therefore, as an attempt to grow O-free III-nitride thin films, we integrated an all stainless steel hollow cathode plasma (HCP) source to the ALD system, and thereby demonstrated the hollow cathode PA-ALD (HCPA-ALD) of wurtzite AIN, GaN and Al x Ga 1-x N thin films with low impurity concentrations at 200 °C [14]. GaN had not been deposited in a self-limiting fashion at such low temperatures since Sumakeris et al [15] reported the growth of GaN using a novel reactor design employing hot filaments to decompose NH 3 in 1993.…”
mentioning
confidence: 99%